Factors influencing the next generations’ succession decisions for family businesses in South Africa - Maduka, Oluchi Jane (University of the Witwatersrand, Johannesburg, 2023)
The involvement of the next-generation family members on succession decisions can improve continuity of the business. i Although several factors scan influence an individuals i choice of career, including in relation to joining the family business, parental support is the most influential. the primary objective of the study was to investigation factors influencing the next-generations’ succession decisions for family i businesses in SA. given that challenges usually emerge during succession decisions especially when the founder wants to pass down the torch to his/her children. This can discontinue the business if a proper process is not instituted.
A research report submitted in partial fulfillment of the requirements for the degree of Master of management in entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Family Business; Succession idecisions; The next-generation; Parental support; Self-efficacy; Commitment ito ithe ifamily ibusiness; SDG-8: Decent work and economic growth